CONSCIOUS PARENTING IN UKRAINE AND FINLAND - Vorozhbit-Gorbatyuk, Victoria; Volkova, Yana; Shtefan, Maryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The current state of upbringing is characterised by a blurring of methodological foundations for understanding the spiritual basis of upbringing of a personality, and an exaggeration of the role of the rational component in this process. We can trace the lack of attention to the social nature of upbringing. The process of upbringing is often excessively individualised and isolated by the framework of a particular person, real living conditions, etc. Such an approach complicates social interaction at the level of personal communication and impedes the integrity of educational influences. The formation of conscious parenthood as a basic value of a civilised society can help to achieve this.A pedagogical retrospection on the valuable pedagogical experience of the past is chosen as one of the information blocks. The idea of developing moral feelings, will and responsibility is revealed through the traditions of Ukrainian folk pedagogy, pedagogical analysis of traditional rituals that accompany the stages of human maturation and are preserved in our time.It is important for Ukraine and Finland to realise that the ideal of education is created in the family circle and its basic values are inner spirituality, ethical responsibility, versatile education, open-mindedness, effective desire for the good of the Motherland, honesty, mercy, charity, gentleness, politeness, restraint, courage and patience in the hardships of life.As a promising direction for developing the issue of conscious fatherhood, we see the creation of opportunities for sharing experiences, forming family and community education traditions, sharing experiences of constructive cooperation between teachers and parents with team-building resources in the implementation of an individual child success programme.